24-Epicastasterone and KH2PO4 protect grain production of wheat crops from terminal heat impacts by modulating leaf physiology. Issue 11 (19th September 2023) - Li, Min; Wei, Qianfei; Zhu, Yulei; Li, Jincai; Ullah, Najeeb; Song, Youhong
ABSTRACT: Heat stress during the grain filling is one of most critical factors impacting grain yield in winter wheat. In a two-year field experiment, we studied the effects of 24-Epicastasterone and KH2 PO4 on heat-stressed wheat applied during different times. A completely randomized block design was used with three reagents, that is, 24-Epicastasterone, KH2 PO4 and H2 O and three spraying times, that is, pre-heat, under-heat and post-heat. Two cultivars, that is, Huaimai 33 and Annong 0711 were subjected to a 7 d post-flowering heat stress using plastic tents. Our study suggests that greater grain weight in heat-stressed plants was achieved through sustaining leaf greenness and higher assimilates supplies to grains. When heat-stressed plants sprayed either with 24-Epicastasterone or KH2 PO4 could sustain a relatively higher leaf photosynthetic capacity by up-regulating antioxidant enzymes with reduced damage on lipid membranes and leaf chlorophyll. We also found that KH2 PO4 was relatively more effective in improving leaf physiology and grain yield of heat-stressed plants than 24-Epicastasterone. Further analysis showed that pre-heat or post-heat was more pronounced in protecting plants from heat injury than spraying the plants under heat stress. Thus, spraying KH2 PO4 either prior to or post stress incidence is recommended to protect wheat crops from terminal heat stress.